Reforming the UN Development System: can North and South overcome their political differences in making the UN fit for purpose? - Max-Otto Baumann (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
In July 2016, Member States of the United Nations (UN) concluded the `ECOSOC Dialogue on the longer-term positioning of the UN Development System' in which they had discussed options for reforming the UNDS for nearly two years. The next step in the reform process will be intergovernmental negotiations on specific reform measures. Against this backdrop, this paper offers a genuinely political analysis of the UNDS and the current reform process. Special emphasis is given to the continuing North-South divide within the UNDS. The paper starts by introducing three theoretical perspectives on the UNDS which emphasize the roles of power, utility and attitudes. These three factors correspond to major shifts in the international development landscape, namely, a global power transformation, the rising need for collective action and a new social context for global cooperation. From these considerations emerges an understanding of the political space and the yardsticks for a successful UNDS reform, whereby success is understood in terms of future political relevancy. In the empirical section, the paper turns to the ECOSOC Dialogue and offers an analysis of major reform options under consideration by Member States in the areas of the `functions', `governance', `funding' and `organization' of the UNDS. The paper concludes by identifying three strategic directions for reform and how Member States should change their behaviour towards the UNDS if they wish to fully exploit the UNDS's comparative advantages as the epitome of multilateral global development cooperation.
Keywords: 330; Regionale + globale + transnationale Governance